RECONFIGURATION MESSAGE HANDLER DALAM MENGATASI RED INDICATOR ALARM PADA SERVER 2 AMSC MEREK COMSOFT DI PERUM LPPNPI CABANG PALEMBANG - Afriandy, aliyah zahra (Cipta Kind Publisher, 2024)
On the Job Training (OJT) activities are the application of knowledge that has been given by lecturers at the Indonesian Aviation Polytechnic Curug. Data communication control device or telex in a computer-based news distribution system that works in a store and forward manner, it called Automatic Message Switching Center (AMSC). News that comes into AMSC is stored and then distributed to the intended address. This system based of civil aviation regulation that used for air traffic safety so that flights are carried out regularly, efficiently and economically. In addition, the AFTN network also functions to exchange news from or between BMKG offices (Meteorology and Geophysics Agency), Notice To Airman (NOTAM), within certain boundaries between airline company offices as well as sending flight data, weather news and other related to the world of aviation. This practice has done of the writer for 5 months at PERUM LPPNPI AIRNAV PALEMBANG. As a result, using Automatic Message Switching Center (AMSC) as a tool for collecting flight information and Aeoronotical Fixed Network (AFTN) which processes all flight data. AFTN is a network system at AMSC that is used for flight data communication between one airport and another by using the address of each airport, both in Indonesia and in other countries in the world.